Kajian Eksistensi Distribusi Hukum Pangkat Pada Kota-Kota di Indonesia - Hoferdy Zawani; Pradono Pradono (The Institute for Research and Community Services, Institut Teknologi Bandung, 2007)
The notion of Power-law which arguably stands for the sign of complex system has been widely encountered in many natural and social phenomenons as upon which we hypothesize Indonesian cities' size distribution would follow the same manner. To evaluate it, we test the hypothesis employing hybrid method co-joined the Cumulative Distribution Function (CDF) technique, Hill Estimator, and Anderson Darling Statistics (Coronel-Brizio, dkk, 2003; Coronel-Brizio and Hernandez-Montoya, 2004) on Indonesian cities' population at year 1990 and 2005. As results, in one hand, our work brings quantitative sight upon Indonesian cities distribution within which were satisfied by Powerlaw distribution for both year 1990 (Xmin=9665 and Alpha=2,088±0,094) and year 2005 (Xmin=129490 and Alpha=1,994±0,078) while in the other hand, it strengthens the precede Power-law Indonesian cities distribution claim which previously proposed by Mulianta, dkk (2004). Put the result altogether and have it tested with deductive and simulation method as we try to explain on how the distribution could ever happen have lead us to conceive the notion of 'onslaught' urbanization in Indonesia. All and all, the work solidifies the edge of chaos paradigm in Indonesian urban and regional planning study.